Ghost squad - Ortega, Claribel A. (Scholastic Inc., 2021)
Lucely and her best friend, Syd, cast a spell just before Halloween that releases evil spirits on their hometown of St. Augustine, Florida. Now they must team up with Syd's witch grandmother, Babette, and her cat Chunk to reverse the spell and save the town before it's too late.